Deficiency mapping of the 93D heat-shock locus in Drosophila melanogaster. - Mohler, J.; Pardue, M.L. (Chromosoma, 1982)
The 93D heat shock locus was mapped relative to an overlapping series of deficiencies of the 93D region by three criteria: the ability of the deleted chromosomes to puff at 93D, the ability of the deleted chromosomes to synthesize RNA from the 93D region after a temperature shift and the presence of heat shock RNA sequences at 93D as assayed by in situ hybridization. The results are essentially the same by all three criteria. Chromosomes with deficiencies that did not extend distal to 93D4 puffed and incorporated 3H-uridine after a temperature shift, and were labelled at 93D following in situ hybridization of heat shock RNA from tissue culture cells. All the other deficiency chromosomes tested failed to puff and to incorporate 3H-uridine following a temperature shift and did not show hybridization in this region after in situ hybridization with heat shock RNA. The heat shock locus was mapped to the overlapping region of Df(3R)eGp4 and Df(3R)GC14 just outside the inverted region of In(3R)GC23.